Representation of Femininity: Grammatical Aspect (Cosmopolitan, Marie Claire and Glamour Magazines) - Beloedova, Anna V.; Khukhryanskaya, Nadezhda N.; Novinkina, Ekaterina A.; Pitinova, Marina Yu.; Shatalova, Yuliya N. (Journal of History Culture and Art Research, 2017)
The paper features the language objectivation of femininity in the glossy magazines Cosmopolitan, Marie Claire and Glamour. The analysis of the problem is based on the theory of the social construction of gender and aims to identify the main trends of language representation of women. The material of the study was Russian Publications Cosmopolitan, Marie Claire and Glamor - the most popular glossy magazines designed for women. The files of the examples analyzed by us are compiled by the method of continuous sampling (more than 2000 contexts) on the basis of printed and Internet versions of Cosmopolitan, Marie Claire and Glamor journals in 2016. The verbal component is considered as one of the main factors in the construction of gender in glossy magazines, which model new type of the "femine" consciousness, combining the sensual experience of reality and the ability to transform it. Gender relations, stereotypes and ideology are revealed through the analysis of linguistic representations. The authors observe morphological and syntax means of the Russian language as indicators of gender identification in terms of mediatext construction. The analysis of language means proves the complication of gender identification in Cosmopolitan, Marie Claire and Glamour, and the sharpening of the "femine" consciousness due to inclusion of masculine features in it. The analysis of linguistic means representing femininity allows to draw a conclusion about the modeling a new type of "female consciousness" on the pages of glossy magazines, in which the ability to the sensual experience of reality is supplemented by the ability to transform it.